A familial case of segregation of motor sensory neuropathy type 1B with multiple exostoses in monozygous twins - V. P. Fedotov; S. A. Kurbatov; S. S. Nikitin; T. B. Milovidova; N. M. Galeeva; A. V. Polyakov (Нервно-мышечные болезни, 2015)
Hereditary motor-sensory neuropathy (MIM 118200) is a rare genetic variant of myelinopathy with autosomal-dominant type of inheritance. Multiple exostosis bones are signs of multiple exostoses chondrodysplasia, genetically heterogeneous form of systemic bone disease with an autosomal dominant mode of inheritance. The combination of two rare autosomal dominant diseases, affecting bone and peripheral nervous system in a pair of monozygotic twins and their father in one family, belongs to a unique clinical observations: since early childhood twins presented sharp reduction of the conduction velocity in all investigated motor nerves (>10 times) together with multiple exostosis bone, confirmed by x-ray with a relatively benign course. Similar manifestations were detected in the patients father. DNA analysis confirmed the presence of 2 separate mutations in 2 different genes, с.389А>G/N gene MPZ and c.678С>А/N EXT2 gene that was inherited autosomal dominant manner, independently of each members of the same family.